Medical Ethnography over Time: Penetrating "the fog of health" in a Nigerian community, 1970–2017. Issue 1 (1st March 2019) - Last, Murray
Abstract : Too often, research into the health of a particular community is brief and superficial, focusing only on what is public and leaving the private health of women and children 'foggy'. By contrast, long-term anthropology can offer access to processes taking place within a local culture of illness. Here, an account of a community's experience of health over the past 50 years not only outlines the key changes as seen anthropologically but also shows how even close ethnography can initially miss important data. Furthermore, the impact of a researcher – both as a guest and as a source of interference – underlines how complex fieldwork can be in reality, especially if seen through the eyes of the researcher's hosts.